Slepkavība pastiprinošos apstākļos - Riekstiņa, Dace (Latvijas Universitāte, 2010)
The theme of this diploma is “ Murder Committed in aggravating Circumstances”. The work consists of the preamble, three parts and the conclusion. In the preamble attention is paid to the place of murder among other crimes. In the first part is given the generalization of the historical evolution of the criminal law in its part of murders - from the Roman law to the Latvian first Republic Punishment Law and the Latvian Criminal Code. In the second part is given the report on murder and its common signs. This crime objective features and subjective features are described in details. In the third part is given a short characteristic of murder with aggravating circumstances. There are few circumstances which are shown in details prescribed in the article Nr.117 of the Latvian Criminal Code: killed woman was pregnant; murder accompanied with robbery; murder accompanied with rape; murder with profit intent; murder of juvenile person. There are shown many problems that concern qualification of murder, also there is an analysis of juridical practice in each case of aggravating circumstances. In conclusion is given an appraisal of changes that prescribed in the Latvian Criminal Code, and also some thoughts about optimizing criminal liability for murder under aggravating circumstances and ensuring legilator’s will common understanding in trial practice.
Murder Committed in aggravating Circumstances
Keywords: Juridiskā zinātne